2013
DOI: 10.4244/eijv8i10a183
|View full text |Cite
|
Sign up to set email alerts
|

Complete Versus culprit-Lesion only PRimary PCI Trial (CVLPRIT): a multicentre trial testing management strategies when multivessel disease is detected at the time of primary PCI: rationale and design

Abstract: The management of multivessel coronary artery disease in the setting of PPCI for STEMI, including the timing of when to perform non-culprit-artery revascularisation if undertaken, remains unresolved. CVLPRIT will yield mechanistic insights into the myocardial consequence of N-IRA intervention undertaken during the peri-infarct period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…For example, patients in the complete revascularization group had more males, had higher door-to-balloon time, and were more likely to suffer from heart failure than those in the culprit artery-only PCI group. These findings are consistent with many other many randomized control studies [2,9,[11][12][13]] the use of percutaneous coronary intervention (PCI The current study results showed that patients in the complete PCI group had 49% lower MACE rate at the mean follow-up of 28 months compared to patients in culprit artery-only PCI group. This finding agrees with the systematic reviews [4,8].…”
Section: R E T R a C T E D A R T I C L Esupporting
confidence: 92%
“…For example, patients in the complete revascularization group had more males, had higher door-to-balloon time, and were more likely to suffer from heart failure than those in the culprit artery-only PCI group. These findings are consistent with many other many randomized control studies [2,9,[11][12][13]] the use of percutaneous coronary intervention (PCI The current study results showed that patients in the complete PCI group had 49% lower MACE rate at the mean follow-up of 28 months compared to patients in culprit artery-only PCI group. This finding agrees with the systematic reviews [4,8].…”
Section: R E T R a C T E D A R T I C L Esupporting
confidence: 92%
“…28,29 This study found that a strategy of complete revascularization before discharge was associated with reduced composite risk of death, recurrent MI, heart failure, or ischemia-driven revascularization at 30 days (HR, 0.45; 95% CI, 0.24-0.84; P=0.009) and the results were sustained ≤1 year. However, there was no statistical significance when each component was analyzed separately.…”
Section: Discussionmentioning
confidence: 65%
“…1,10 A network meta-analysis has suggested that multivessel staged PCI may be associated with a better outcome than multivessel primary PCI, 11 but such data are still insufficient to inform a recommendation with regard to the optimal timing of non-culprit vessel PCI. [12][13][14] In fact, a more recent meta-analysis showed that CR at the index procedure or as a staged procedure -whether during hospitalisation or after discharge -was associated with a reduction in the risk of adverse events, although the effect was mostly due to a reduction in the risk of urgent revascularisation. There was no difference between various strategies in the risk of all-cause mortality and spontaneous reinfarction at a median of 25 months.…”
Section: 210mentioning
confidence: 99%